Application of Mossbauer and positron annihilation spectroscopies for monitoring of WWER RPV steel degradation. (14th January 2008) - Slugen, V.; Lipka, J.; Hascik, J.; Krsjak, V.; Petriska, M.; Zeman, A.
This paper describes the application of Mossbauer Spectroscopy (MS) and Positron Annihilation Spectroscopy (PAS) to evaluate the microstructure parameters of materials. These methods are used to collect additional characteristics for understanding of degradation processes in Reactor Pressure Vessel (RPV) steels. Samples from the Russian 15Kh2MFA and Sv10KhMFT steels, commercially used at WWER-440 reactors, were irradiated near the core at NPP Bohunice (Slovakia) to neutron fluences in the range 7.8 ? 1023 m−2 to 2.5 ? 1024 m−2. Systematic changes in the MS and PAS spectra were observed mainly during the early period of irradiation. These could be due to changes caused by the precipitation of elements such as Cu, P or Cr, mainly in carbides to the surface. The MS results confirm that the close environment of Fe atoms in the body-centred cubic lattice of RPV steels remain almost stable after initial changes and can be correlated with the ductile?brittle transition temperature curve from mechanical tests. Positron annihilation lifetime measurements using the Pulsed Low Energy Positron System (PLEPS) were applied for investigation of defects of irradiated and thermally treated RPV steels. Results showed that the changes in the microstructure of the RPV-steel properties caused by neutron irradiation and postirradiation thermal treatment can be detected in the surface as well as the bulk region.